Pollution control and resource reuse for alkaline hydrometallurgy of amphoteric metal hazardous wastes - Zhao, Youcai; Zhang, Chenglong (Springer, 2017)
This book provides a comprehensive description of alkaline hydrometallurgy of amphoteric metal hazardous wastes. Topics focus on leaching of zinc and lead hazardous wastes, purification of leach solution of zinc and lead, electrowinning of zinc and lead from purified alkaline solutions, chemical reactions taking place in the production flowsheets, thermodynamic and spent electrolyte regeneration, alkaline hydrometallurgy of low-grade smithsonite ores, recovery of molybdenum and tungsten using ion flotation and solvent extraction processes and their application in chemical synthesis of Nb and Ta inorganic compounds, and industrial scale production of 1500-2000 t/a zinc powder using alkaline leaching?electrowinning processes. Processes described are cost-effective, generate lesser secondary pollutants, and have been applied widely in China. Readers that will find the book appealing include solid waste engineers, environmental managers, technicians, recycling coordinators, government officials, undergraduates and graduate students, and researchers.
Keywords: Hazardous waste site remediation.; Hazardous wastes.; elektronické knihy; electronic books